2017
DOI: 10.1021/acs.langmuir.6b04546
|View full text |Cite
|
Sign up to set email alerts
|

pH Switchable Emulsions Based on Dynamic Covalent Surfactants

Abstract: Dynamic covalent surfactants were designed to prepare pH switchable emulsions. A dynamic covalent bond between nonamphiphilic building blocks (polyethylenimine (PEI) and benzaldehyde (B)) was introduced to form the dynamic covalent surfactant PEI-B. The dynamic nature of covalent bond in PEI-B was confirmed by H NMR and fluorescence probe analysis. Stable emulsions were successfully prepared with interfacial active PEI-B at pH 7.8 with various water/paraffin oil ratios under sonication. When lowering the pH to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 48 publications
2
44
0
Order By: Relevance
“…changes in droplet size or stability. [12][13][14] In contrast, Janus emulsions, i.e. droplets comprised of two dispersed fluids, have the intrinsic advantage that interfacial tension variations transduce into a change in the internal shape of the droplets whereas the overall emulsion stability remains intact.…”
Section: Introductionmentioning
confidence: 99%
“…changes in droplet size or stability. [12][13][14] In contrast, Janus emulsions, i.e. droplets comprised of two dispersed fluids, have the intrinsic advantage that interfacial tension variations transduce into a change in the internal shape of the droplets whereas the overall emulsion stability remains intact.…”
Section: Introductionmentioning
confidence: 99%
“…In some applications, it is acceptable to lock the polymer self‐assemblies permanently; however, the ability to manipulate the self‐assemblies based on external stimuli is a highly attractive reason to instead employ dynamic crosslinking strategies. The use of responsive and highly functional building blocks to make block copolymers allows for their assembly and disassembly, in addition to their changing shapes or sizes based on external stimuli . It has been demonstrated that polymer micelles are more readily uptaken into cells than their unimers, and as a result, acid‐degradable polymers have been a focus in polymer cancer therapy developments .…”
Section: Introductionmentioning
confidence: 99%
“…The use of responsive and highly functional building blocks to make block copolymers allows for their assembly and disassembly, 18 in addition to their changing shapes or sizes based on external stimuli. 11,19,20 It has been demonstrated that polymer micelles are more readily uptaken into cells than their unimers, 21 and as a result, aciddegradable polymers have been a focus in polymer cancer therapy developments. 15,22 In addition to pH as a stimulus, polyelectrolytes have been used to reversibly lock micelles using electrostatic interactions and electrolytes as stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Responsive emulsifiers have emerged as a class of smart surfactants that permit regulating the emulsion stability under external stimuli [4][5][6][7][8]. The external stimuli include pH [9][10][11][12][13][14][15], CO 2 [6,16], temperature [17], magnetism [8], light [18,19], and redox [7,20]. Among these external stimulation types, pH has attracted particular interest because it has the advantage of being simple to regulate [11,21].…”
Section: Introductionmentioning
confidence: 99%